The reception of Northrop Frye - Denham, Robert D. (University of Toronto Press, 2021)
Frontmatter -- Contents -- Introduction -- Chapter 1 Books and Symposia -- Chapter 2 Essays, Articles, and Parts of Books -- Part 1 -- Part 2 -- Chapter 3 Obituaries, Memorials, Tributes -- Chapter 4 News and Feature Stories, Miscellaneous Items -- Chapter 5 Biographical Notices and Articles -- Chapter 6 Reviews of Frye’s Books, Excluding Those in the Collected Works -- Chapter 7 Reviews of the Volumes in Frye’s Collected Works -- Chapter 8 Dissertations and Theses on Frye -- Appendix: Frye’s Books: Editions and Translations